Biological Maturation, Central Adiposity, and Metabolic Risk in Adolescents: A Mediation Analysis - Werneck, André O.; Silva, Danilo R.; Collings, Paul J.; Fernandes, Rômulo A. [UNESP]; Ronque, Enio R.V.; Barbosa, Décio S.; Cyrino, Edilson S. (SAGE Publications, 2016)
Background: Earlier biological maturation has been related to increased metabolic risk. In this study, we verified mediating effects by central adiposity of the relationship between somatic maturity and metabolic risk factors in adolescents. Methods: In a cross-sectional study, 1034 adolescents aged 10-16 years from Londrina/PR/Brazil were evaluated. The age of peak height velocity (PHV) method was used to evaluate somatic maturity. Central adiposity was estimated through waist circumference measurements. Fasting glucose, triglycerides, high-density lipoprotein cholesterol (HDL-C), and blood pressure were measured as metabolic risk indicators. Physical activity (Baecke questionnaire) and cardiorespiratory fitness (20-m shuttle run test) were used as covariates. Results: Except for fasting glucose, waist circumference showed partial or full mediation of the relationship between maturity and the following metabolic risk factors with their respective z-score values: triglycerides (boys =-3.554 vs. girls =-5.031), HDL-C (boys = +5.300 vs. girls = +5.905), systolic blood pressure (boys =-3.540 vs. girls =-3.763), diastolic blood pressure (boys =-2.967 vs. girls =-3.264), and metabolic risk score (boys =-5.339 vs. girls =-6.362). Conclusions: The results suggest that central obesity plays a mediating role in the relationship between somatic maturation and metabolic risk during adolescence.